Gambaran Histopatologi Selaput Lendir Kantung Empedu Sapi Bali yang Terinfeksi Cacing Fasciola gigantica (HISTOPATOLOGICAL ILLUSTRATION OF GALL BLADDER MUCOUS MEMBRANE INFASCIOLA GIGANTICA INFECTED BALI CATTLE) - Kardena, I Made; Winaya, Ida Bagus Oka; ., Elyda; Adhiwitana, I Dewa Made; Adi, AAA Mirah; Berata, I Ketut (Jurnal Veteriner, 2016)
This study aims were to describe lesions and their intensities of histopathological changes in gallbladder mucosa of bali cattle that infected with Fasciola gigantica. As many as 42 gall bladers of balicattle were used in this studi, i.e: 35 samples were infected and sefen were non-infected with F.gigantica.The samples were randomly gathered from Pesanggaran slaughter house in Denpasar. The gall bladderswere evaluated macroscopically and prepared for microscopically examination using haematoxylin andeosin staining.The result showed that there were histopathological changes observed in the mucosa of thegall bladder:necrosis cells of gall bladder with intencity 100%, hemorrhage 68.5%, hyperplasia serousgland and mucous hypertrophy gland 100%, collagen in filtration 100%, fibroblast proliferation 91.4%,and infiltration of inflammation cells, 74.2%. Histopathological changes in gallbladders mucous of balicattle infected F.gigantica experiencing severe lesons with frequency percentage above 50%.
Keywords: Fasciola gigantica; gall bladder; bali cattle